Angiotensin II phosphorylation of extracellular signal regulated kinases in rat anterior pituitary cells - Suárez, Cecilia Ana (2003)
We studied the effects of ANG II on extracellular signal-regulated kinase (ERK)1/2 phosphorylation in rat pituitary cells. ANG II increased ERK phosphorylation in a time- and concentration-dependent way. Maximum effect was obtained at 5 min at a concentration of 10-100 nM. The effect of 100 nM ANG II was blocked by the AT1 antagonist DUP-753, by the phospholipase C (PLC) inhibitor U-73122, and by the MAPK kinase (MEK) antagonist PD-98059. The ANG II-induced increase in phosphorylated (p)ERK was insensitive to pertussis toxin blockade and PKC depletion or inhibition. The effect was also abrogated by chelating intracellular calcium with BAPTA-AM or TMB-8 by depleting intracellular calcium stores with a 30-min pretreatment with EGTA and by pretreatment with herbimycin A and PP1, two c-Src tyrosine kinase inhibitors. It was attenuated by AG-1478, an inhibitor of epidermal growth factor receptor (EGFR) activation. Therefore, in the rat pituitary, the increase of pERK is a Gq- and PLC-dependent process, which involves an increase in intracellular calcium and activation of a c-Src tyrosine kinase, transactivation of the EGFR, and the activation of MEK. Finally, the response of ERK activation by ANG II is altered in hyperplastic pituitary cells, in which calcium mobilization evoked by ANG II is also modified.